Risk Management: In an Overview of Literature Review - Endah Suci Damayanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to provide an overview of risk management in various industries with different objectives through academic papers and then for researchers to voice their opinions. The methods are literature-based and qualitative. The results of this study provide an overview and complement further work with other investigators. Researchers found little evidence for this. The recommendations for this study come from areas other than financial risk management, as many researchers do. The researchers hope that other researchers will use other variables in future studies, such as environmental destruction, the financial sector, and other variables in other financial sectors.